(Cation)2C2O4∙nSnPh2C2O4(n=1, 2; cation=Pr2NH2, MeNH3) AND SOME OF THEIR ADDUCTS: SYNTHESIS, INFRARED AND MOSSBAUER STUDIES - YAYA SOW; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Three [SnPh2(C2O4)2]2- containing new adducts have been synthesized and characterized by elemental analyses, infrared and Mossbauer spectroscopy, the suggested structures being discrete, the SnPh2 residues octahedral cis or trans coordinated. A trans [SnPh2(C2O4)2]2- complex- anion has been evidenced by spectroscopic methods for the first time in this work. The new complex-anion [SnPh2Cl(C2O4)2]3- with a seven coordinated tin centre has been reported in this paper and a two metallic components structure containing a tetranuclear and a mononuclear components with octahedral environments around the tin centers interacting with cations and involving OH groups leading to a supramolecular architecture has also been reported. The anion behaves as a mono- or a bichelating ligand.